ANALYSIS ON EFL LEARNERS’ CAPABILITY IN MASTERING TOEFL TEST ON READING COMPREHENSION - Hizbul Wathoni; Bambang Purnama; Hanofi Harianto; Ari Safar Wadi; Selamet Riadi Jaelani; Bq. Sartika Ningsih (UIBU, 2022)
This research aimed at knowing learners’ capability in mastering TOEFL test on reading comprehension part for EFL Learners. It was a descriptive quantitative research. It was conducted at the fourth semester students of EFL Learners as the sample of research. The class consisted of 3 classes and the sampling used of this research was cluster random sampling by lottery the class. The sample was class A consisted of 25 EFL Learners. In collecting the data, the instrument was given in the form of reading comprehension of TOEFL test and it was consisted of 50 items dealing with mastering main idea, mastering explicit implicit information, mastering reference, mastering meaning of word, and mastering inferences. After collecting the data, it was analyzed descriptive statistics by operating SPSS 26 for windows to know the mean score of students’ test. The mean score of the test was 32.3. It was categorized into very low. Therefore, the students of EFL Learners had very low capability in answering TOEFL reading comprehension section. Therefore, it is significantly for the students who have low ability in reading comprehension to mastering the strategies in answering the reading test.